Unmet need for family planning and associated factors, among women of child-bearing age working in Hawassa industrial park, Southern Ethiopia 2021: An institution based cross-sectional study - Elias Amaje; Tatek Ayalew (Elsevier, 2022)
Background: Despite the negative consequence of the unmet need for family planning no study has been conducted on women working in the industrial parks. Therefore this study aimed to determine the prevalence of unmet need for family planning and its associated factors among women in reproductive age working in Hawassa industrial park. Methods: An institution-based cross-sectional study was conducted from July 1 to 30/2021 among randomly selected 405 women working in Hawassa industrial park. Data was collected using face-to-face interviews using a pre-tested structured questionnaire. The data was entered into Epi-data 3.1 and exported to SPSS Version 24 for statistical analysis. Bivariable and multivariable logistic regression analyses were used to identify factors associated with the unmet needs for family planning. Independent factors associated with the unmet need for family planning were assessed using AOR with their corresponding 95% CIs at P-value < 0.05 cut of point. Result: In this study, the prevalence of unmet need for family planning was 27.7% (95% CI 23.2 to 32.3). Educational status [AOR = 4.53; CI (1.62, −12.61)], marital status (AOR = 7.2; 95% CI: (3.77, 13.73)], residence [AOR = 0.56; 95% CI: (0.31, 0.99)], and knowledge of family planning [AOR = 0.36; 95% CI: (0.20, 0.63)] were independent predictors of unmet need for family planning. Conclusion: This study found that the prevalence of unmet needs for family planning was high. Educational status, marital status, residence, and knowledge of family planning were significantly associated with unmet needs of family planning.